Leading in a non-linear world building wellbeing, strategic and innovation mindsets for the future - Gomes, Jean (Ascent Audio, 2023)
Leading in a Non-Linear World leads listeners through a groundbreaking set of science-based strategies to help them face rising demand, uncertainty and change posed by disruptive technologies and seismic shifts in globalization. The book shows how our mindset, more than our knowledge and expertise, has the potential to be our greatest asset in facing the future. Jean Gomes reviews the latest brain research revealing that our mindset is the interplay of feeling, thinking, and seeing, and how we can build it to significantly increase our wellbeing and performance. Leading in a Non-Linear World provides listeners with a new science-based definition of mindset and the tools to: build and strengthen their mindset; increase their sustainability and wellbeing; understand and build the ultimate strategic mindset; learn how to create the mindset that's foundational to the success of the world's fastest growing companies; and how to build an open mindset that allows leaders to create flexible, adaptive cultures capable of naturally responding to change. Perfect for CEOs, Chief Innovation Officers, business leaders, digital officers, and anyone in a managerial or supervisory role, Leading in a Non-Linear World shows leaders how to shift their thinking and realize explosive growth in a world that demands nothing less.